The Evidence Base on the Efficacy and Safety of Ibuprofen in Pediatrics - Yu.V. Marushko; Yu.I. Todyka; I.I. Garbar (Zaslavsky O.Yu., 2013)
The article deals with an analysis of the world literature of recent years, the aim of which was to study the efficacy and safety of ibuprofen use as first-line antipyretic in pediatric practice. Special attention was paid to researches on the study the pharmacokinetics, efficacy and safety of ibuprofen in fever in children of all ages, as well as the use of different forms of ibuprofen (suspension, suppositories).